Board profile and earnings quality: Malaysian evidence / Marini Mamat and Azizah Abdullah - Mamat, Marini; Abdullah, Azizah (2013)
Investors and potential investors normally rely on the information contain in financial statement to make investment decision. These suggest that shareholders of company are concerned with board of directors’ characteristics that might influence the reliability of financial accounting report. This paper examines how multiple directorships, financial expertise and board experience affect the quality of reported earnings. The sample consists of 113 MSWG ranked companies for the year 2007, 2008 and 2009. Using OLS, the results show that financial expertise and board experience are positively related to earnings quality in top 150 MSWG ranked companies. Overall, these results provide evidence that boards are important elements affecting the quality of financial report, particularly quality of earnings.